Does the European Union achieve comprehensive blue growth? Progress of EU coastal states in the Baltic and North Sea, and the Atlantic Ocean against sustainable development goal 14 - Wilfried Rickels; Christian Weigand; Patricia Grasse; Jörn Schmidt; Rüdiger Voss (Marine policy, 2019)
The Sustainable Development Goal for the oceans and coasts (SDG 14) as part of the 2030 Agenda can be considered as an important step towards achieving comprehensive blue growth. Here, we selected a set of 18 indicators to measure progress against SDG 14 for 15 EU coastal countries in the Baltic and the North Sea and the Atlantic Ocean since 2012. In our assessment we distinguish between a concept of weak and strong sustainability, assuming high and low substitution possibilities, respectively. Our results indicate that there are countries which managed to achieve sustainable development under both concepts of sustainability (most notably Estonia, achieving the strongest improvement), but that there are also countries which failed to achieve sustainable development under both concepts (most notably Ireland and Belgium, experiencing the strongest decline). Unsustainable development is in particular driven by increasing fishing mortality and reduced willingness to set total allowable catch in accordance with scientific advice.
Keywords: 330; Sustainable development goals; Blue growth; European Union; Fisheries